A Systematic Literature Review on the Exploration of the Impact of English Media on Vocabulary Development in Bilingual Toddlers - Agnes Monica Rahayu; Adrefiza; Failasofah (Universitas Islam Negeri Palopo, 2025)
This systematic literature review looks into how bilingual children vocabulary development is affected by their exposure to English media. The early years of childhood, from 1 to 6 years old, are the most pivotal time for language development, impacted by social, environmental, and biological factors. Bilinguals' vocabulary development is usually impacted by a number of aspects, such as media exposure, home literacy environments, and parental participation. Using the PRISMA 2020 framework, five studies published from Januart 2021 to March 2025 were selected from three databases; Google Scholar, ERIC, and Taylor & Francis. Results indicate that interactive and socially supported media use can successfully improve L2 vocabulary, whereas passive media exposure alone may impede language development. Furthermore, the context, quality, and adult supervision of media intake have a significant effect on language results.